Draft genome sequence of immunobiotic Lactobacillus rhamnosus strain IBL027, a potential adjuvant for mucosal vaccine development - Vizoso Pinto, María Guadalupe (2017)
The genome sequence of the immunomodulatory strain Lactobacillus rhamnosus strain IBL027 is described here. The reads were assembled into contigs with a total size 2,898,501 bp. The genome information will be useful for further specific genetic studies of this strain to evaluate its immunomodulatory and biotechnological properties as a vaccine adjuvant.